Combating Obesity With Thermogenic Fat: Current Challenges and Advancements - Pan, Ruping; Zhu, Xiaohua; Maretich, Pema; Chen, Yong (Frontiers in Endocrinology, 2020)
Brown fat and beige fat are known as thermogenic fat due to their contribution to non-shivering thermogenesis in mammals following cold stimulation. Beige fat is unique due to its origin and its development in white fat. Subsequently, both brown fat and beige fat have become viable targets to combat obesity. Over the last few decades, most therapeutic strategies have been focused on the canonical pathway of thermogenic fat activation via the β3-adrenergic receptor (AR). Notwithstanding, administering β3-AR agonists often leads to side effects including hypertension and particularly cardiovascular disease. It is thus imperative to search for alternative therapeutic approaches to combat obesity. In this review, we discuss the current challenges in the field with respect to stimulating brown/beige fat thermogenesis. Additionally, we include a summary of other newly discovered pathways, including non-AR signaling- and non-UCP1-dependent mechanisms, which could be potential targets for the treatment of obesity and its related metabolic diseases.